2017
DOI: 10.1021/acssuschemeng.6b02850
|View full text |Cite
|
Sign up to set email alerts
|

Filling Single-Walled Carbon Nanotubes with Lutetium Chloride: A Sustainable Production of Nanocapsules Free of Nonencapsulated Material

Abstract: Filled carbon nanotubes are of interest for a wide variety of applications ranging from sensors to magnetoelectronic devices and going through the development of smart contrast and therapeutic agents in the biomedical field. In general, regardless of the method employed, bulk filling of carbon nanotubes results in the presence of a large amount of external nonencapsulated material. Therefore, further processing is needed to achieve a sample in which the selected payload is present only in the inner cavities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In a recent example, Nieto et al adapted a previously reported protocol [25,26] to encapsulate viologen derivatives in 1.6-2.2-nm-thick metallic SWCNTs causing a band-gap opening of the nanomaterials [27]. Following a completely different approach, Kierkowicz et al prepared SWCNTs filled with LuCl 3 whose radioactive isotope 177 Lu is largely used in medicine [28]. To do so and in line with most recent reports, SWCNTs were purified i.e., (i) oxidation; (ii) acid treatment to remove the catalyst; and (iii) annealing to restore the graphitic nature) and then grinded in the presence of the salts.…”
Section: Catalysts 2018 8 X For Peer Review 3 Of 20mentioning
confidence: 99%
“…In a recent example, Nieto et al adapted a previously reported protocol [25,26] to encapsulate viologen derivatives in 1.6-2.2-nm-thick metallic SWCNTs causing a band-gap opening of the nanomaterials [27]. Following a completely different approach, Kierkowicz et al prepared SWCNTs filled with LuCl 3 whose radioactive isotope 177 Lu is largely used in medicine [28]. To do so and in line with most recent reports, SWCNTs were purified i.e., (i) oxidation; (ii) acid treatment to remove the catalyst; and (iii) annealing to restore the graphitic nature) and then grinded in the presence of the salts.…”
Section: Catalysts 2018 8 X For Peer Review 3 Of 20mentioning
confidence: 99%
“…Chemical vapour deposition SWCNTs (Elicarb ® ) were provided by Thomas Swan & Co. Ltd. (Consett, UK) with an average diameter of 2.1 nm (value provided by the supplier). LuCl 3 @SWNCTs were prepared following the protocol previously described [ 27 ]. Briefly, pristine SWCNTs were steam treated at 900 °C for 4 h followed by an HCl wash [ 28 ], which leads to a median length of 420 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, the encapsulation protocol involves using a large excess of filler (compared to the available space inside the nanotubes). During the filling procedure the material not only crystallizes within the inner channels of the nanotubes, but also a significant amount of the inorganic precursor remains external to the carbon nanotubes [24,25]. Since the presence of external material will generally interfere with the properties of the sample, further washing is required to clean the nanotubes.…”
Section: Selected Examples Of Confined Na Nocrystalsmentioning
confidence: 99%
“…Having samples free of external material allows the quantitative determination of the encapsulated compounds [26]. It has been experimentally shown that the material encapsulated within narrow SWCNT and few-walled CNT by melt filling cannot be removed during the washing step, even when harsh conditions are involved [25,27]. This is because the ends of the CNTs close upon cooling, thus inhibiting the dissolution of the crystals [28].…”
Section: Selected Examples Of Confined Na Nocrystalsmentioning
confidence: 99%